La revolución sandinista en imágenes. El episodio de la toma del búnker de Somoza en la lente de Pedro Valtierra. Nicaragua, 1979 - Mónica Morales Flores (Centre de Recherches sur les Mondes Américains, 2012)
The capture of the bunker (July, 1979) marked the end of Anastasio Somoza’s dictatorship and the victory of the Sandinista Revolution. A set of images of this fact, recorded by Pedro Valtierra, was published by the Mexican newspaper unomásuno. This paper analyzes how thess photographic images were diffused, comparing oral testimonies, newspaper and photography archives.